"Hazy" or "jumbled"? Putting together the pieces of the bilingual puzzle. Issue 3 (15th March 2016) - García-Pentón, Lorna; Fernández García, Yuriem; Costello, Brendan; Duñabeitia, Jon Andoni; Carreiras, Manuel
ABSTRACT: Six commentaries [Bialystok, E. (2015). How hazy views become full pictures. Language, Cognition and Neuroscience . doi:10.1080/23273798.2015.1074255 ; de Bruin, A., & Della Sala, S. (2015) The importance of language use when studying the neuroanatomical basis of bilingualism. Language, Cognition and Neuroscience. doi:10.1080/23273798.2015.1082608 ; Green, D. W., & Abutalebi, J. (2015). Language control and the neuroanatomy of bilingualism: In praise of variety. Language, Cognition and Neuroscience . doi:0.1080/23273798.2015.1084428 ; Kroll, J. and Chiarello, C. (2015). Language experience and the brain: Variability, neuroplasticity, and bilingualism. Language, Cognition and Neuroscience . doi:10.1080/23273798.2015.1086009 ; Luk, G., & Pliatsikas, C. (2015). Converging diversity to unity: Commentary on the neuroanatomy of bilingualism. Language, Cognition and Neuroscience ; Paap, K. (2015). The neuroanatomy of bilingualism: Will winds of change lift the fog? Language, Cognition and Neuroscience . doi:10.1080/23273798.2015.1082607 ] were produced in relation to the review "The neuroanatomy of bilingualism: How to turn a hazy view into the full picture" (García-Pentón, L., Fernández, Y., Costello, B., Duñabeitia, J. A., & Carreiras, M. (2015). The neuroanatomy of bilingualism: How to turn a hazy view into the full picture. Language, Cognition and Neuroscience . doi:10.1080/23273798.2015.1068944 ). In the review, we argued that the available evidence for structural changes in bilingualism offers ambiguous support for current neural models of bilingualism and that this shortcoming in the field is exacerbated by critical methodological differences between studies. Thus, best practices need to be established for studying and modelling bilingualism. The commentaries bring to the discussion new perspectives and highlight additional challenges. Our response addresses the issues raised under two broad topics: the need to connect structural findings with behavioural and functional data, and a series of methodological concerns that are critical if the field is to advance.